2011
DOI: 10.1136/bmj.d3403
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal sleep practices and risk of late stillbirth: a case-control study

Abstract: Objectives To determine whether snoring, sleep position, and other sleep practices in pregnant women are associated with risk of late stillbirth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
144
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(161 citation statements)
references
References 32 publications
13
144
2
2
Order By: Relevance
“…In our study, a PT intervention was implemented in a population of healthy, third-trimester, pregnant women during sleep in a clinical sleep laboratory environment over two nights. This study extends the work of Stacey et al ,2 Gordon et al ,3 McCowan et al ,4 and Warland and Mitchell52 by finding that supine sleep position in late pregnancy can be reduced with PT.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, a PT intervention was implemented in a population of healthy, third-trimester, pregnant women during sleep in a clinical sleep laboratory environment over two nights. This study extends the work of Stacey et al ,2 Gordon et al ,3 McCowan et al ,4 and Warland and Mitchell52 by finding that supine sleep position in late pregnancy can be reduced with PT.…”
Section: Discussionsupporting
confidence: 86%
“…A recent study of questionnaires on maternal sleep practices reported that the risk of stillbirth among pregnant women sleeping on the left side was lower than the risk among women sleeping supine or on the right side [21]. The reason was thought to be related to the anatomical position of the inferior vena cava and the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…A controversial observation has been reported recently in a case-control study in which women who slept on their back or on their right side the previous night (before fetal death) had a higher rate of late stillbirth than women who slept on their left side (aOR for back sleeping, 2.54; 95% CI, 1.04-6.18). 124 An editorial commenting on this article concluded that the study should be considered hypothesis-generating rather than hypothesis-testing. 125 The puzzling observation was that women who got up to go to the toilet once or less on the last night before the diagnosis of stillbirth were more likely to have a late fetal death than those who got up more frequently.…”
Section: Maternal Sleep Position and Late Stillbirthmentioning
confidence: 99%